(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
Background: Type 2 diabetes mellitus (T2DM) is associated with impairments in foot posture, balance, and functional performance, which may be further influenced by aging. However, age-related differences in response to exercise interventions remain insufficiently explored. Objective: To evaluate age-stratified effects of a structured exercise program on foot posture, balance, and functional performance in individuals with T2DM. Methods: In this controlled, age-stratified study, 54 participants with T2DM were allocated to an exercise (n=27) or control group (n=27) and further stratified into middle-aged (40–59 years) and older (60–80 years) subgroups. The intervention consisted of an 8-week structured physiotherapy program. Outcomes included Foot Posture Index (FPI), static balance (center of gravity sway on firm surface), dynamic balance (Limits of Stability), and functional performance (6-minute walk test), assessed at baseline, 4 weeks, and 8 weeks. Results: The exercise group demonstrated significant improvements in foot posture, balance, and functional performance compared to controls (p < 0.05). FPI scores improved toward neutral alignment, while static and dynamic balance showed reduced sway and enhanced stability. Functional performance improved significantly, exceeding clinically meaningful thresholds. Age-stratified analysis revealed greater improvements in foot posture among middle-aged participants, whereas balance and functional gains were observed across both age groups, with comparable improvements in older adults. Conclusion: Structured exercise significantly improves foot posture, balance, and functional performance in individuals with T2DM. While age influences the magnitude of structural adaptation, functional and balance improvements are preserved in older adults, supporting the use of exercise interventions across age groups.